Enhancing teacher agentic learning in physics education: The impact of cognitively guided instruction on prospective teachers' cognitive engagement - Iwuanyanwu, Paul Nnanyereugo (Indonesian Journal of Science and Mathematics Education, 2024)
This study aims to explore the impact of teacher agentic learning applied through the Cognitively Guided Instruction (CGI) approach on the cognitive engagement of prospective physics teachers in thermodynamics laboratory activities, specifically in determining the coefficient of performance of a heat pump. This study employs a one-group pre-post design. Thirty-eight prospective physics teachers participated in a three-week learning program with pre-test and post-test assessments measuring their knowledge of thermodynamics concepts, problem-solving abilities, and experimental data evaluation. The results showed a significant improvement in teacher agentic learning, reflected in their abilities to manage cognitive resources, solve cognitive tasks, and evaluate experimental data more effectively. Statistical tests indicated a significant increase (t = –0.129, p = 0.001). Thus, CGI can enhance the agentic learning of prospective physics teachers. The implications of this study emphasize the importance of applying agentic-based learning in physics education to improve critical thinking skills and understanding of more complex physics concepts.